COVID-19 Vaccination in Pregnancy and Lactation: Current Research and Gaps in Understanding - Shook, Lydia L.; Fallah, Parisa N.; Silberman, Jason N.; Edlow, Andrea G. (Frontiers in Cellular and Infection Microbiology, 2021)
The COVID-19 pandemic has demonstrated the urgent need to develop vaccine strategies optimized for pregnant people and their newborns, as both populations are at risk of developing severe disease. Although not included in COVID-19 vaccine development trials, pregnant people have had access to these vaccines since their initial release in the US and abroad. The rapid development and distribution of novel COVID-19 vaccines to people at risk, including those who are pregnant and lactating, presents an unprecedented opportunity to further our understanding of vaccine-induced immunity in these populations. In this review, we aim to summarize the literature to date on COVID-19 vaccination in pregnancy and lactation and highlight opportunities for investigation that may inform future maternal vaccine development and implementation strategies.